Smart Sensor with network plug and play capabilities - Sharovar, Igor (University of Ottawa (Canada), 2004)
This thesis proposes enhancements to the network capabilities of the IEEE 1451.1 standard. The IEEE 1451.1 standard belongs to the popularly used, innovative group of specifications called Smart Sensor. It defines a standardized way to design and develop transducers that can be easily connected to a sensor network. The IEEE 1451.1 standard defines a Common Object Model, which may be used to design the network capability of a Smart Sensor device, but does not define a standard way to connect Smart Sensor devices to different types of networks. A variety of modern technologies is applied today, allowing ease with which network devices connect to networks. One such technology is Universal Plug and Play (UPnP), which defines the mechanism and protocol for the discovery of network devices, as well as their control and event functions. The goal of this thesis is to expand the IEEE 1451.1 standard to make Smart Sensor devices capable of working as UPnP devices. Achieving this will enable the design of an UPnP Smart Sensor that will not only connect different types of transducers to a sensor network, but will also provide a standard and easy mechanism to connect these devices to different networks, including the Internet, while minimizing the effort required for their design and implementation.
Keywords: Engineering, Electronics and Electrical.